Local Communities’ Awareness and Perceptions of Astro-tourism in Tanzania: A Case of Mbozi Meteorite - Mushy, Reguli Baltazar (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2024)
Tourism is one of the fastest growing economic sectors and the largest industries in the world. Among the many branches of tourism that this study considers is nature-based tourism, with a particular emphasis on a special interest tourism product referred to as astro-tourism. Astro-tourism focuses on activities related to observing night skies and celestial phenomena in natural spaces, as well as terrestrial meteorites relicts. Astronomical views such as rainbows, beautiful sunsets, sunrises, and astronomical phenomenon such as solar and lunar eclipses can attract many tourists all around the world. In Tanzania, the Mbozi Meteorite (kimondo) is emerging as an opportunity for tourism destination in the country. The main objective of this study was to assess local communities’ perceptions and awareness of Mbozi meteorite as one of the aspects of astro-tourism. A mixed research approach with questionnaires, in-depth interviews and observations was used to collect data from 110 respondents who were randomly selected for the study from local communities/villages in the neighbourhoods of Mbozi meteorite site. 15 key informants were purposefully selected from Songwe region including local community leaders/elders, tourism entrepreneurs (Agents, tour guides, shopkeepers, curio, art & crafts), and government officials. Both descriptive and thematic analyses were used to analyze quantitative and qualitative data. Findings revealed that the local community members are aware of the presence of kimondo, and they associate it with varied taboos and traditions. Further they noted that despite being there for decades, it is just of recent that kimondo has attracted attention and attracted a number of visitors and tourists. The number of tourists has increased in the locality hence bringing up new opportunities and threats. The study recommends for community education and involvement in tourism activities that will improve their livelihoods.